Novel Concepts of Altered Immunoglobulin G Galactosylation in Autoimmune Diseases - Dekkers, Gillian; Rispens, Theo; Vidarsson, Gestur (Frontiers in Immunology, 2018)
The composition of the conserved N297 glycan in immunoglobulin G (IgG) has been shown to affect antibody effector functions via C1q of the complement system and Fc gamma receptors (FcγR) on immune cells. Changes in the general levels of IgG-glycoforms, such as lowered total IgG galactosylation observed in many autoimmune diseases have been associated with elevated disease severity. Agalactosyslated IgG has therefore been regarded and classified by many as proinflammatory. However, and somewhat counterintuitively, agalactosylation has been shown by several groups to decrease affinity for FcγRIII and decrease C1q binding and downstream activation, which seems at odds with this proposed proinflammatory nature. In this review we discuss those circumstances where altered IgG galactosylation/glycosylation is found. We propose a novel model based on these observations and current biochemical evidence, where the levels of IgG galactosylation found in the total bulk IgG affect the threshold required to achieve immune activation by autoantibodies through either C1q or FcγR. Although this model needs experimental verification, it is supported by several clinical observations and reconciles apparent discrepancies in the literature, and suggests a general mechanism in IgG-mediated autoimmune diseases.